Extensive Computed Tomography versus Limited Screening for Detection of Occult Cancer in Unprovoked Venous Thromboembolism: A Multicenter, Controlled, Randomized Clinical Trial - Prandoni, Paolo; Bernardi, Enrico; Valle, Fabio Dalla; Visonà, Adriana; Tropeano, Pietro F.; Bova, Carlo; Bucherini, Eugenio; Islam, Md Shahidul; Piccioli, Andrea (Seminars in Thrombosis and Hemostasis, 2016)
Patients with unprovoked venous thromboembolism (VTE) may harbor occult cancer. Whether an extensive diagnostic work-up for cancer has additional value over a more limited screening for detection of underlying malignancy in these patients is controversial. We performed a randomized multicenter trial to assess if in patients with unprovoked VTE, a computed tomography (CT)-based diagnostic strategy including thoracic, abdominal, and pelvic CT in combination with fecal occult blood test yields a higher cancer detection rate than a nonstandardized testing approach based on physicians' clinical judgment and patients' preferences. Cancer-free patients were followed up for up to 24 months. Of the 195 consecutive patients with unprovoked VTE who were eligible for this investigation, an occult cancer was identified in 10 of the 98 patients (10.2%) randomized to the CT-based strategy, and in 8 of the 97 (8.2%) allocated to the personalized strategy (absolute difference, 2.0%; 95% confidence interval, −7.2–11.1; p = 0.81). During follow-up, cancer was identified in an additional 2 patients in each group. Overall, 7 (7.1%) patients of the CT-based strategy died, as compared with 11 (11.3%) of the personalized strategy, with 2 and 4, respectively, due to cancer. In conclusion, a CT-based strategy in combination with fecal occult blood test does not provide a clinically significant benefit over more limited cancer screening for detecting occult cancer in patients with unprovoked VTE. (ClinicalTrials.gov number, NCT00361647).
Keywords: venous thromboembolism; cancer; diagnostic screening; computed tomography